Signal Radiation leakage of power line Communication Systems - Sekyere, Francois (2011)
A Thesis submitted to the Department of Telecommunication Engineering, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Science